Effect of ripasudil after trabeculectomy with mitomycin C: a multicentre, randomised, prospective clinical study - Muhlisah, Aisyah; Hirooka, Kazuyuki; Nurtania, Ariyanie; Onoe, Hiromitsu; Okumichi, Hideaki; Nitta, Eri; Baba, Tetsuya; Tanito, Masaki; Matsuoka, Yotaro; Nakakura, Shunsuke; Kiuchi, Yoshiaki (BMJ open ophthalmology, 2024)
BackgroundTo investigate if there are improvements in trabeculectomy outcomes supporting filtration bleb formation caused by Rho-associated protein kinase (ROCK) inhibitors.MethodsThis prospective, multicentre, randomised, open-label clinical study examined open-angle glaucoma patients who underwent trabeculectomy or trabeculectomy combined with cataract surgery followed by 3-month postoperative ripasudil treatments. After randomly allocating patients to ripasudil—ROCK inhibitor (ripasudil) or without ripasudil (non-ripasudil) groups. Mean intraocular pressure (IOP) changes, success rate, and number of eyedrops were compared for both groups.ResultsA total of 17 and 15 subjects dropped out in the ripasudil group and non-ripasudil group, respectively. At baseline, the mean IOP was 16.8±5.0 mm Hg in the ripasudil group (38 patients) and 16.2±4.4 in the non-ripasudil group (52 patients). The IOP decreased to 11.4±3.2 mm Hg, 10.9±3.9 mm Hg and 10.6±3.5 mm Hg at 12, 24 and 36 months in the ripasudil group, while it decreased to 11.2±4.1 mm Hg, 10.5±3.1 mm Hg and 10.9±3.2 mm Hg at 12, 24 and 36 months in the non-ripasudil group, respectively. There was a significant decrease in the number of IOP-lowering medications after trabeculectomy in the ripasudil group versus the non-ripasudil group at 24 (p=0.010) and 36 months (p=0.016). There was no statistically significant difference between the groups for the 3-year cumulative probability of success.ConclusionAlthough ripasudil application did not increase the primary trabeculectomy success rate, it did reduce IOP-lowering medications after trabeculectomy with mitomycin C.